Pengaruh Variasi Suhu Penekanan Terhadap Kualitas dan Sifat Mekanik Serat Daun Nanas Berbasis Resin Epoksi untuk Aplikasi Komposit - Roni Suhartono; Yadi Hikmah Setiana; Didin Komarudin (CV. IRA PUBLISHING, 2025)
This study aims to evaluate the effect of varying pressing times at a constant temperature, using the hot-press method and the same resin mixture, on the material's quality and mechanical properties. Tensile testing was conducted in accordance with ASTM D3039 using specimens measuring 250 × 20 × 2 mm to ensure accurate mechanical measurements on thin laminates. The process began with selecting healthy pineapple leaves, followed by extrusion. A chemical treatment was then applied by immersing the fibers in a 5% NaOH solution for 2 hours. The fibers were subsequently mixed with resin and pressed for 20, 30, and 40 minutes at 100 °C. The results showed that the first sample, pressed for 40 minutes, achieved a tensile strength of 55.25 MPa. The second sample, pressed for 30 minutes, reached 50.38 MPa, while the third sample, also pressed for 30 minutes, achieved 47.8 MPa. The 40-minute pressing time can be considered the recommended working point, as evidenced by the highest tensile strength of 55.25 MPa.